IMPROVEMENT OF CONTAINERIZED OAK SEEDLINGS CULTIVATION TECHNOLOGY - Danilenko, O. N.; Tarnopilsky, P. B.; Gladun, G. B. (Forestry and Forest Melioration, 2018)
Introduction Effective microorganisms come into use in forestry gradually. The results of growth of containerized oak seedlings using microbial fertilizers are presented in the paper. Mineral feeding of substrate complex mineral fertilizers during the growth of seedlings that intensify the growth of seedlings in containers is usually used. Information on bacterial fertilizers inoculation of substrates in containers during seedlings growing is very poor. The aim of the study is to establish the efficiency of microbial fertilizers in growing containerized oak seedlings. Materials and Methods Studies were conducted at the greenhouse complex of Danilyvske Research Forestry of URIFFM in 2011-2014. Oak seedlings (Quercus robur L.) were grown in containers using the technology developed by scientists of URIFFM, on the soil + peat (3: 1) substrate in the open ground with irrigations. In experiments with using microbial fertilizes for oak seedlings growing, Azotobakteryn (10 g/l), Polimiksobakteryn (10 ml/l and 20 ml/l), Ryzobrazyn (40 ml/l), Biophyte (15 ml/l), Hetomik (1 ml/l), Baikal (100 ml/l) were used in “pure” form as well as with the addition of Humate (1.5 g/l), ammonium nitrate (0,3% ) Agrolife (5 g/container) and NPK fertilizer (40 g/m2). Fertilization was performed be wetting on the basis of 5 l spray material of product on 1 m2 of containers. Results We tested Azotobakteryn, Polimiksobakteryn, Ryzobrazyn in the first year of experiments. The most positive effect on height and root collar diameter of seedling was produced by Polimiksobakteryn. Exceeding of these indices over control was 29 and 33 %, respectively. Polimiksobakteryn fertilizing contributed to a statistically significant increase in weight of tree trunk by 132 % and the root mass by 82 %. We tested Biophyte, Hetomik, Baikal and Polimiksobakteryn in 2012-2013. All kinds of microbial agents which we used contributed to a significant stimulation of growth of oak seedlings by height (16-32 %), by the diameter of the root collar (8-19 %), by weight of tree trunk (46-89 %) and root (on 18-59 %). In 2014 treatment of the substrate in containers by Baikal contributed statistically reliable increase in seedlings height (60 %) and root length (15 %) over the control. In all variants of the experiment, adding mineral fertilizers to Baikal had a positive impact on the growth of oak seedlings in height, increasing the diameter of the root collar and root length. However, the best results were obtained in Baikal + ammonium nitrate 0.3 % variant. The height of oak seedlings was higher over the control by 93 %, root collar diameter by 24 %, root length by 23%. Similarly with biometric indicators, we also noted an increase in air-dry weight of seedlings and in the experiment. Substrate fertilizing by Polimiksobakteryn 20 ml/l + Humate 1,5 g/l and Baikal 1 : 100 + Humate 1,5 g/l as aqueous suspensions twice during the vegetation period: immediately after planting acorns in the substrate and after the appearance of two or three true leaves, as well as Baikal with mineral fertilizers was the most effective of the test preparations. Conclusions In most cases, fertilizing of containerized oak seedlings by microbial fertilizers improved the growth of aboveground parts, as well as the root system in the experiments. Taking into account the fact that the seedlings are planted in containers in silvicultural area together with substrate inoculated with beneficial live microorganisms one can predict their positive aftereffect on the growth of forest plantations.